Cognitive status is a determinant of health resource utilization among individuals with a history of falls: a 12-month prospective cohort study. Issue 3 (March 2016) - Davis, J.; Dian, L.; Khan, K.; Bryan, S.; Marra, C.; Hsu, C.; Jacova, P.; Chiu, B.; Liu-Ambrose, T.
Abstract Summary Falls are a costly public health problem worldwide. The literature is devoid of prospective data that identifies factors among fallers that significantly drive health care resource utilization. We found that cognitive function—specifically, executive functions—and cognitive status are significant determinants of health resource utilization among older fallers. Introduction Although falls are costly, there are no prospective data examining factors among fallers that drive health care resource utilization. We identified key determinants of health resource utilization (HRU) at 6 and 12 months among older adults with a history of falls. Specifically, with the increasing recognition that cognitive impairment is associated with increased falls risk, we investigated cognition as a potential driver of health resource utilization. Methods This 12-month prospective cohort study at the Vancouver Falls Prevention Clinic (n = 319) included participants with a history of at least one fall in the previous 12 months. Based on their cognitive status, participants were divided into two groups: (1) no mild cognitive impairment (MCI) and (2) MCI. We constructed two linear regression models with HRU at 6 and 12 months as the dependent variables for each model, respectively. Predictors relating to mobility, global cognition, executive functions, and cognitive status (MCI versus no MCI) were examined. Age, sex, comorbidities, depression status, and activities of daily living were included regardless of statistical significance. Results Global cognition, comorbidities, working memory, and cognitive status (MCI versus no MCI ascertained using the Montreal Cognitive Assessment (MoCA)) were significant determinants of total HRU at 6 months. The number of medical comorbidities and global cognition were significant determinants of total HRU at 12 months. Conclusion MCI status was a determinant of HRU at 6 months among older adults with a history of falls. As such, efforts to minimize health care resource use related to falls, it is important to tailor future interventions to be effective for people with MCI who fall. Trial registration ClinicalTrials.gov Identifier:NCT01022866 .